Challenges In Early Childhood Development in The Digital Screen Era - Nuruliana, Hernawati; Zulkarnaen, Z (Universitas Muhammadiyah Surakarta, 2025)
Purpose: This study examines the challenges of early childhood development in the digital screen era at Al A'raaf Islamic Kindergarten. The purpose of this study is to determine the challenges of early childhood development in the digital screen era. Methodology: The research method used a qualitative approach with a descriptive qualitative model. Data were collected through observation and interviews with 5 teachers and 5 parents at Al A'raaf Islamic Kindergarten. Data analysis techniques used three steps, namely data reduction, data presentation, and conclusion drawing. Results: The results showed changes in motor, cognitive, language, and social-emotional aspects, such as poor motor coordination, low concentration, delayed speech, decreased emotional control, and limited interaction with friends.Applications/Originality/Value: Not only were there negative effects, but there were also positive effects, namely that children could easily recognize colors, letters, and numbers and enrich their vocabulary if digital screens were used according to rules and age appropriateness. It can be concluded that there are not only negative effects, but digital screens can also have positive effects if accompanied by time management, parental guidance, and quality content.